Design, synthesis, biological evaluation, and docking study of new acridine‐9‐carboxamide linked to 1, 2, 3‐triazole derivatives as antidiabetic agents targeting α‐glucosidase. (6th October 2020) - Asgari, Mohammad S.; Tahmasebi, Behnam; Mojtabavi, Somayeh; Faramarzi, Mohammad A.; Rahimi, Rahmatollah; Ranjbar, Parviz R.; Biglar, Mahmood; Larijani, Bagher; Rastegar, Hossein; Mohammadi‐Khanaposhtani, Maryam; Mahdavi, Mohammad
Abstract: A new series of acridine‐9‐carboxamide‐1, 2, 3‐triazole derivatives 7a‐m were designed, synthesized, and evaluated as novel α‐glucosidase inhibitors. Acridine‐9‐carboxamide‐1, 2, 3‐triazole scaffold has been designed by combination of effective moieties from potent α‐glucosidase inhibitors. Most of the synthesized compounds were more potent than standard inhibitor acarbose. Among the title compounds, the most potent compounds were compounds 7j, 7k, and 7a with IC50 values of 120.2 ± 1.0, 151.1 ± 1.4, and 157.6 ± 1.6 μM, respectively (IC50 value of acarbose = 750.0 ± 10.0 μM). Docking study of the most potent compounds demonstrated that these compounds formed stable complexes with α‐glucosidase active site. Anti‐α‐amylase assay of compounds 7j, 7k, and 7a was performed and no activity was observed. in vitro cytotoxicity assay of the latter compounds revealed that these compounds were not cytotoxic toward human normal (HDF) and cancer (MCF‐7) cell lines. ADME and toxicity prediction of compounds 7j, 7k, and 7a were also performed. Abstract :